Influência da exposição perinatal ao inseticida fipronil: repercussão tardia em parâmetros reprodutivos masculinos e femininos, em ratos - Barros, Aline Lima de [UNESP] (2015)
Fipronil is an insecticide widely used in agriculture, veterinary medicine and public health, and recently has been listed as a possible endocrine disruptor. Studies demonstrate that this compound can affect the thyroid function, reproductive parameters and central nervous system. However, most of studies performed with fipronil evaluated the acute toxicity, and a few of them refer to its reproductive effects, especially if the exposure occurs during gestation and lactation. This study aimed to evaluate the effects resulting from perinatal exposure to fipronil and its possible late repercussion on male and female reproductive parameters, in rats. Pregnant rats received three doses of fipronil (0.03; 0.3 or 3 mg/kg) from gestational day 15 to postnatal day 7, by gavage. During the treatment, water and food consumptions as well as the body weight of females exposed were investigated. After weaning, we collected the blood of mothers for biochemical analysis and the organs to verify the weight. The male offspring was evaluated for body weight, anogenital distance and ages of preputial separation and testicular descent. At adult life, weight of reproductive organs, sperm counts, morphology and motility, testicular and epididymal histomorphometry, sertoli cells count, sexual behavior and preference, fertility and patterns of expression of androgen receptor in the testis were evaluated. On female offspring was investigated anogenital distance, puberty onset, estrous cycle, hormonal levels, fertility, sexual behavior and histology of uterus and ovaries. The treatment did not alter the biochemical parameters and the weight of most of analyzed organs of mothers exposed to fipronil, however the weight of pituitary gland presented a reduction in the group exposed to a lower dose. On males, the perinatal exposure to fipronil did not affect the body weight, anogenital distance and puberty onset. Similarly, at adult life, fipronil did not alter the organ...